A Comparative Study of Desarda's Technique with Lichtenstein Mesh Repair in Treatment of Inguinal Hernia - Tausif Ahmad, Liaquat Ali Khan, Farman Khan, Noorshad Khan, Muhammad Wajid, Ifranullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: European hernia society (EHS) published a guideline that recommended Lichtenstein method for inguinal hernia repair. Currently Lichtenstein method is considered the most popular method. Desarda repair technique was used for the first time in 2001 which is still not considered as a standard tissue-based technique for inguinal hernia repair. We compared Desarda's technique with Lichtenstein mesh repair technique in treatment of inguinal hernia repair. Objectives: To compare the outcome of standard mesh-based Lichtenstein technique with the tissue based Desarda technique in terms of pain. Materials and Methods: After taken approval from hospital ethical committee, 250 patients were enrolled in the study. Enrolled patients were divided into two group. Group A underwent hernia repair through Desarda technique & group B will underwent hernia repair through Lichtenstein technique. Post-operative pain was assessed on day 7 and 30 by using visual analogue scale. All information was recorded on a pre-designed Proforma. The collected data from the patients through Proforma’s was entered in SPSS. Results: 250 patients were included in our study with mean age distribution 42.18+10.34 year. 82.8% patients were males while 17.2% were females. Mean SD of operative time for both groups (Desarda Group vs Lichtenstein Technique) were 23.41+ 0.17 vs 24.18 + 0.66. 111) patients (89%) 92 felt mild post-operative pain who were subjected to Group A while 14 (11%) patients suffered moderate post-operative pain with Mean SD 2.46+0.30. 88% patients felt post-operative pain who were subjected to Group B while 15 patients (12%) felt moderate post-operative pain with Mean SD 2.46+0.18 thus giving us almost same results as found in Group A. Conclusion: The results of inguinal hernia treatment with both Desarda and Lichtenstein technique are similar. So, we conclude the Desarda repair is as effective as the standard Lichtenstein procedure, allowing successful hernia repair without mesh in terms of pain. Keywords: Desarda's technique, Lichtenstein mesh, inguinal hernia